Republic of Estonia : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper on the Republic of Estonia highlights its growth performance relative to other countries in the European Union (EU). Estonia has experienced a period of unprecedented growth since the mid-1990s. Between 1995 and 2005, Estonia's real GDP per capita rose by an average of 6 1\2 percent a year, exceeding the annual growth rates of all other countries in the EU. This impressive growth performance is partly explained by the recovery from the immediate post-central planning drop in output.